2013
DOI: 10.3109/13625187.2013.801072
|View full text |Cite
|
Sign up to set email alerts
|

Child desire in women and men living with HIV attending HIV outpatient clinics: Evidence from a European multicentre study

Abstract: Many women and men living with HIV in Europe desire children and have fertility intentions, for which they need unbiased support to conceive and deliver safely. Comprehensive and gender-specific sexual and reproductive health counselling, including pre-conception and contraceptive counselling, should be integrated into HIV care delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…This finding agrees with that of a multicenter study in Europe, which showed that 43% of those interviewed reported a desire for a child and factors associated with this desire included being younger than 36years of age [9]. This finding is also consistent with findings of several studies [6], [7], [8].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This finding agrees with that of a multicenter study in Europe, which showed that 43% of those interviewed reported a desire for a child and factors associated with this desire included being younger than 36years of age [9]. This finding is also consistent with findings of several studies [6], [7], [8].…”
Section: Discussionsupporting
confidence: 83%
“…These variables include: age, age range, gender, duration of marriage, number of children, level of education, income, residence (urbanity and rurality) history of extramarital affairs, alcohol use, viral subtype [6], [7], [8]. A multicenter study by Nostlinger and colleagues, showed that 43% of the interviewees reported a desire for a child and factors associated with this desire included being younger than 36 (both male and female) and the fact that the couple had no child at all [9]. An exploratory study in Brazil, corroborated that women who had many children who were alive did not want to have more children [10].…”
Section: Introductionmentioning
confidence: 99%
“…3 The need and desire for FP services is substantial among HIV-positive persons in both resource-limited [4][5][6][7][8][9][10] and resource-rich [11][12][13][14] settings. The unmet need for FP services is particularly high in Kenya; one study found that nearly 70% of HIV-positive women in western Kenya indicate wishing to delay their fertility for another 2 years or not have any further children.…”
mentioning
confidence: 99%
“…In a qualitative study, 93% of participating women in South Carolina had no desire to become pregnant due to concerns about HIV transmission to the fetus, financial instability, single relationship status, age, and previous childbearing or child rearing experiences [ 72 ]. A European study that explored satisfaction with sexual and reproductive health services reported that 58% of all participants (59% of sample were in a serodiscordant couple) were not satisfied with services delivered in HIV care settings, while a third of participants reported HIV-related discrimination in healthcare settings [ 73 ]. Qualitative work conducted in Northern Ireland found that love, commitment, physical pleasure, and a desire to conceive without medical interventions helped to shape perceptions of risk within the relationship [ 74 ].…”
Section: Resultsmentioning
confidence: 99%